Marketing technology and literacy as key drivers of SME market penetration - M Arief Setia Budi; Muhammad Andi; M Thoyib Maulana (Journal of Innovation in Business and Economics, 2025)
This study investigates the role of technology accessibility in marketing activities as a mediating variable between marketing literacy and the availability of marketing technology in enhancing market penetration. It also examines the moderating effect of entrepreneurs’ internal perceptions of the benefits of marketing technology on the relationship between technology accessibility and market penetration. The research involved 225 entrepreneurs from the small and medium enterprise (SME) sector across various regions of Aceh Province and was analyzed using AMOS Structural Equation Modeling (SEM). The results demonstrate that marketing literacy, the availability of marketing technology, and the accessibility of such technology in marketing activities significantly contribute to increased market penetration. Furthermore, technology accessibility is confirmed to mediate the influence of the independent variables on the dependent variable. Internal perceptions of the benefits of technology have also been found to quasi-moderate the relationship between marketing technology accessibility and market penetration.